Cardiac stunning as first manifestation of multiple sclerosis: A case report reminding us not to overlook cardiovascular autonomic dysfunction in multiple sclerosis - Hilz, Max-Josef (Multiple sclerosis journal, 2016)
Autonomic dysfunction is common but frequently overlooked in multiple sclerosis (MS) patients. The case of a Tako-Tsubo cardiomyopathy on which this commentary is based shows that centrally triggered autonomic dysfunction may be the first life-threatening manifestation of MS.
EVALuna2:22462